DIAGNOSIS OF RESPIRATORY RHYTHM BASED ON PHYSIOLOGICAL PARAMETERS OF PLETHYSMOGRAPHY USING ARTIFICIAL INTELLIGENCE - Болобан, Олег (SWorldJournal, 2024)
This article discusses the problem of diagnosing respiratory rhythm based on physiological indicators of plethysmography using artificial intelligence. Diseases of the respiratory system are becoming more common, especially after the COVID-19 epidemic. T